Evaluation of the neonatal sepsis diagnosis: use of clinical and laboratory parameters as diagnosis factors - Meireles, Luciano de Assis; Vieira, Alan Araújo; Costa, Carolina Roella (Revista da Escola de Enfermagem da USP, 2011)
The purpose of this study was to describe and compare the clinical, laboratory and health care characteristics of newborns (NBs) with confirmed late onset sepsis and NBs with unconfirmed late sepsis, verify if there were any differences between the groups, and describe the germs prevalent in the studied neonatal unit. This is a descriptive study, involving 168 cases. It was observer that 33.3% had a confirmed diagnosis for late onset sepsis. The age at the time of sepsis onset, the length of stay, the total number of neutrophils, the number of immature neutrophils and the value of PC-r proved good parameters to differentiate between the two groups when analyzed separately. The most common isolated bacteria were: Klebsiella pneumoniae, Staphylococcus coagulase negative and S. aureus.